The Effect of Mind Map-Assisted Guided Inquiry on Students' Critical Thinking in Earth Science - Sri Maharani; Skunda Diliarosta; Ade Sazaliana (PT. Komunitas Peneliti Alinea, 2026)
Students at SMPN 2 Pariaman demonstrate relatively low critical thinking skills, mainly due to teacher-centered instructional practices that limit students' active participation and the limited use of innovative learning models and instructional media, particularly in teaching abstract science concepts. This study aimed to investigate the effect of the Guided Inquiry learning model supported by Mind Map media on the critical thinking skills of eighth-grade students studying Earth's Structure and Its Development. A quasi-experimental method with a Nonequivalent Control Group Design was employed. The sample consisted of 62 students selected through purposive sampling and divided into an experimental group, which received Guided Inquiry instruction assisted by Mind Map media, and a control group, which received conventional instruction. Data were collected using a validated critical thinking test, observation sheets, and a student response questionnaire and were analyzed using descriptive and inferential statistical techniques. The findings revealed that students taught through the Guided Inquiry model integrated with Mind Map media demonstrated significantly better critical thinking skills than those who experienced conventional learning. Furthermore, the implementation of the learning model and students' responses were categorized as good, indicating that the approach was effectively implemented and positively accepted. These findings suggest that integrating Guided Inquiry with Mind Map media is an effective strategy for fostering students' critical thinking skills in science learning, particularly on the topic of Earth's Structure and Its Development.